2021
DOI: 10.1177/23821205211014895
|View full text |Cite
|
Sign up to set email alerts
|

A Better Learning Community: Mixed-Methods Reveal Medical Student Preferences with Implications for Learning Community Design and Implementation

Abstract: Background: Medical school learning communities benefit students. The College of Medicine (COM) at the University of Arkansas for Medical Sciences (UAMS) provides medical students with academic, professional, and personal support through a learning community (LC) made of 7 academic houses. Objectives: To evaluate the effectiveness of the academic house model at UAMS utilizing a mixed-methods survey. The aims were to: (1) assess student experience and satisfaction with academic houses, (2) describe the realms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…This competence is echoed in the literature. A recent survey of mentees who matched into plastic surgery residencies found that items related to a genuine interest in the mentee’s career and personal development and a willingness to set aside time for teaching as the highest-rated attributes (Ahmady et al, 2020; Barker et al, 2016; Braunreiter et al, 2022; Frosch & Goldstein, 2019; Vuk et al, 2021). The mentees from the same study also stressed the importance of one-on-one time with their mentor and listed mentors’ time constraints as a substantial barrier to the mentorship relationship (Barker et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This competence is echoed in the literature. A recent survey of mentees who matched into plastic surgery residencies found that items related to a genuine interest in the mentee’s career and personal development and a willingness to set aside time for teaching as the highest-rated attributes (Ahmady et al, 2020; Barker et al, 2016; Braunreiter et al, 2022; Frosch & Goldstein, 2019; Vuk et al, 2021). The mentees from the same study also stressed the importance of one-on-one time with their mentor and listed mentors’ time constraints as a substantial barrier to the mentorship relationship (Barker et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Students benefit from career guidance by faculty members, increased networking opportunities, and leadership development (P. D. North CS et al, 2005). Learning communities have been found to be associated with medical student empathy and well-being (Tackett et al, 2018; Vuk et al, 2021). Faculty member participation in LCs improves the clinical skills, productivity, job satisfaction, and communication abilities of the mentors (Ferguson et al, 2009; Osterberg et al, 2016; Smith et al, 2014, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…By engaging in communities that prioritise continuous education, students develop a mindset of curiosity, inquiry, and self-improvement that prepares them for post-graduate training and their future career in the workplace. 3 , 16 , 17 It is also often assumed that the training and knowledge acquired in medical training as a student, and the often unstructured practical work and teaching experience gained post-graduation in the clinical setting, is sufficient for preparing practitioners for specialist training. 18 This perhaps highlights the lack of continuity in teaching and learning approaches as students migrate from undergraduate education into further health professions education as a postgraduate.…”
Section: Designing Learning Communitiesmentioning
confidence: 99%
“… 20 It is also essential to develop appropriate evaluation methods to assess the effectiveness and impact of LCs as this is essential for continuous improvement. 17 Formal mechanisms to obtain regular student and staff feedback for quality improvement purposes will help those already using LCs adjust to the recommendations and needs of all involved in the communities. This is also important as maintaining the long-term sustainability of LCs requires ongoing support, faculty development, and integration within the broader curriculum.…”
Section: Designing Learning Communitiesmentioning
confidence: 99%
“…A survey of medical schools that are members of the LCI reported that the most frequently cited objectives of LCs were to provide advising and mentoring, professional development, course offerings in clinical skills and medical humanities, social activities, and wellness [ 18 ]. LCs provide a supportive home to students outside the rigors of the necessary sciences [ 19 ].…”
Section: Introductionmentioning
confidence: 99%